2022
DOI: 10.3390/antiox11091793
|View full text |Cite
|
Sign up to set email alerts
|

The Catalase KatA Contributes to Microaerophilic H2O2 Priming to Acquire an Improved Oxidative Stress Resistance in Staphylococcus aureus

Abstract: Staphylococcus aureus has to cope with oxidative stress during infections. In this study, S. aureus was found to be resistant to 100 mM H2O2 during aerobic growth. While KatA was essential for this high aerobic H2O2 resistance, the peroxiredoxin AhpC contributed to detoxification of 0.4 mM H2O2 in the absence of KatA. In addition, the peroxiredoxins AhpC, Tpx and Bcp were found to be required for detoxification of cumene hydroperoxide (CHP). The high H2O2 tolerance of aerobic S. aureus cells was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Previous analyses showed that the catalase KatA and the peroxiredoxin AhpCF could compensate for each other in H 2 O 2 detoxification in S. aureus ( 33 , 34 ). Indeed, the ∆ katA ∆ ahpC double mutant was significantly impaired in growth upon HOSCN stress in relation to the WT, supporting that antioxidant enzymes protect against HOSCN-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous analyses showed that the catalase KatA and the peroxiredoxin AhpCF could compensate for each other in H 2 O 2 detoxification in S. aureus ( 33 , 34 ). Indeed, the ∆ katA ∆ ahpC double mutant was significantly impaired in growth upon HOSCN stress in relation to the WT, supporting that antioxidant enzymes protect against HOSCN-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the Δ merA mutant, only the Δ katA Δ ahpC double mutant was sensitive toward HOSCN stress. However, the absence of KatA and AhpC affects aerobic growth due to the hypersensitivity of the Δ katA Δ ahpC mutant toward H 2 O 2 stress ( 33 , 34 ). Since overexpression of KatA and AhpC in the Δ perR mutant did not provide a growth advantage under HOSCN stress, the role of the antioxidant enzymes KatA and AhpC in protection against HOSCN-induced ROS formation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Q6PXX2 and Q9EV50 (katA) proteins are catalases that induce the conversion of H 2 O 2 to H 2 O in bacteria ( Linzner et al, 2022 ). It has been found that disruption of katA can lead to increased levels of ROS in Proteus mirabilis , resulting in increased bacterial susceptibility to H 2 O 2 and reduced biofilm biomass ( White et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gram-stained S. aureus bacteria displayed purple coloration under a 1000x magnification microscope and a clustered, spherical morphology that is typical of Staphylococcus germs (Kobayashi et al, 2020). A positive catalase test result means that the bacteria are either aerobic or facultatively anaerobic, meaning that they use oxygen to breathe (Linzner et al, 2022). A positive coagulase test result means S. aureus can produce coagulase enzymes that can cause the activation of nonproteolytic pro-thrombin and fibrinogen cleavage (Trivedi et al, 2018).…”
Section: Bacterial Isolatesmentioning
confidence: 99%